EVALUATING TOLL-ROAD REVENUE PERFORMANCE AND RISK FACTORS THROUGH MONTE CARLO SIMULATION: CASE-BASED LEARNING IN ENGINEERING ECONOMICS - Fiska Chintya Ezra Pangalila; CLAUDIA TALITA DARIWU; Kindly Anugerah Imanuel Pangauw (EDUCATIONE, 2026)
Although the Manado–Bitung Toll Road is a National Strategic Project intended to improve connectivity and logistics efficiency in North Sulawesi, realized revenues have not yet covered operating and maintenance expenditures, raising uncertainty about investment recovery within the 50-year concession period. This study evaluates the project’s financial feasibility based on realized revenue performance and examines how key risk factors influence break-even and payback prospects. Using realized financial data from October 2020 to June 2025, the analysis applies cash-flow assessment, Break-Even Point (BEP), and Payback Period indicators, complemented by Quantitative Risk Analysis (QRA) with Monte Carlo simulation to model uncertainty in revenue growth, policy conditions, user behavior, and maintenance costs. The findings show cumulative revenue of IDR 232.75 billion against operating costs of IDR 253.56 billion, resulting in a persistent cash-flow deficit and a negative interim BEP. Monte Carlo outputs suggest that break-even is most likely to occur near the end of the concession (around year 48), with an estimated profitability probability of only 28% under the current trajectory, and the most influential risks are annual revenue growth and government policy/regulation, followed by user behavior and maintenance-cost escalation. The study concludes that while the project has high strategic value, it is not financially feasible in the medium term without intervention; therefore, policy support is needed to strengthen Bitung SEZ-driven logistics demand, improve traffic capture, and implement structured risk mitigation and efficiency measures. Future research should incorporate discounted cash-flow metrics (NPV/IRR), test alternative policy scenarios (tariff adjustments and incentives), and integrate broader socio-economic benefits into investment appraisal.